2008
DOI: 10.1162/jocn.2008.20137
|View full text |Cite
|
Sign up to set email alerts
|

Differential Lateralization for Words and Faces: Category or Psychophysics?

Abstract: This set of three experiments assessed the influence of different psychophysical factors on the lateralization of the N170 event-related potential (ERP) component to words and faces. In all experiments, words elicited a left-lateralized N170, whereas faces elicited a right-lateralized or nonlateralized N170 depending on presentation conditions. Experiment 1 showed that lateralization for words (but not for faces) was influenced by spatial frequency. Experiment 2 showed that stimulus presentation time influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
51
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 60 publications
(102 reference statements)
11
51
0
1
Order By: Relevance
“…Also, neutral words elicited larger amplitudes at PO7 than at P8 and O2. These findings were consistent with left-lateralized word N170 found in previous researches (Mercure et al, 2008;Rossion et al, 2003). However, different pattern emerged with regard to fat-and thin-related words in WD group.…”
Section: Negative Bias Toward Fatness-related Words During Early Procsupporting
confidence: 92%
“…Also, neutral words elicited larger amplitudes at PO7 than at P8 and O2. These findings were consistent with left-lateralized word N170 found in previous researches (Mercure et al, 2008;Rossion et al, 2003). However, different pattern emerged with regard to fat-and thin-related words in WD group.…”
Section: Negative Bias Toward Fatness-related Words During Early Procsupporting
confidence: 92%
“…Consistently, studies using ERPs reveal a stronger N170 component in the LH over the RH in response to printed words (for recent examples, see Maurer, Rossion, & McCandliss, 2008;Mercure, Dick, Halit, Kaufman, & Johnson, 2008), and neuroimaging studies have identified a region of the inferior temporal cortex, the Visual Word Form Area ( VWFA), that shows greater selectivity for words over other visual stimuli, especially in the LH Cohen et al, 2000;Puce, Allison, Asgari, Gore, & McCarthy, 1996). Finally, individuals with LH vOT lesions are impaired in word reading ("pure alexia") to a greater degree than is the case after a lesion to the homologous RH region (e.g., Behrmann & Plaut, 2013a;Kleinschmidt & Cohen, 2006).…”
Section: Lateralization Of Words In Right-handersmentioning
confidence: 53%
“…However, no learning effect was observed in the right LO (t (11) ϭ Ϫ1.43, p Ͼ 0.05). The failure of observing the learning effect in the right LO might be caused by the hemispheric asymmetry in object perception, because the left hemisphere prefers objects with high-spatial frequency and the right hemisphere shows an opposite advantage (Sergent, 1983;Grabowska and Nowicka, 1996;Mercure et al, 2008). The stimuli in this study were high-contrast line-drawing objects that are preferred stimuli for the left hemisphere, whereas previous studies that reported the learning effect in the right LO used objects with smoothed surfaces in object discrimination tasks (Grill-Spector et al, 2000;Op de Beeck et al, 2006).…”
Section: The Role Of Task Context In Object Learningmentioning
confidence: 62%